Promoting Vegetable Intake in Preschool Children: Does Enhancing the Taste of Vegetables Influence the Portion Size Effect?. (29th May 2020) - Diktas, Hanim; Keller, Kathleen; Roe, Liane; Sanchez, Christine; Rolls, Barbara
Abstract: Objectives: To meet dietary guidelines, effective strategies are needed to encourage children to eat a greater proportion of their diet from vegetables. We tested whether serving a larger portion, enhancing the taste with small amounts of butter and salt, or combining these strategies would increase vegetable intake at a meal for preschool children. Methods: Using a crossover design in childcare centers, we served lunch once a week for four weeks to 67 children aged 3–5 y (61% girls; 16% with overweight or obesity). The meal consisted of two familiar vegetables (broccoli and corn) along with fish sticks, rice, ketchup, applesauce, and milk. Across the four meals, we varied the portion of vegetables (60 or 120 g total weight) and served them either plain or enhanced (0.5% salt and 6.6% light butter by weight). The other items in the meal were not varied. All meals were consumed ad libitum and weighed to determine intake. At the end of the study, children rated their liking for the foods and parents completed questionnaires about their child's eating behavior. Results: Doubling the portions of vegetables led to greater consumption of both broccoli and corn ( P  < 0.0001) and increased total vegetable intake by 68% (mean ± SEM 21 ± 3 g). Enhancing vegetables with butter and salt, however, did not influence their intake ( P  = 0.13) nor modify the effect of larger portions on their intake ( P  = 0.10). Serving more vegetables did not affect intake of the other meal components ( P  = 0.57), thus meal energy intake increased by 13 ± 5 kcal (5%; P  = 0.02). Ratings indicated that children had similar liking for the plain and enhanced versions of both broccoli ( P  = 0.31) and corn ( P  = 0.97). Although 73% of children rated one or both plain vegetables as yummy or just okay, they ranked their preference for the other foods in the meal higher than for the vegetables ( P  < 0.0001). Children differed in their response to larger portions of vegetables: those with higher scores for food fussiness and parental pressure to eat had smaller increases in vegetable intake when portions were doubled (both P  < 0.03). Conclusions: Serving larger portions of vegetables at a meal was an effective strategy to promote vegetable intake in children. When familiar, well-liked vegetables were served, adding butter and salt was not necessary to increase vegetable consumption. Funding Sources: National Institute of Diabetes and Digestive and Kidney Diseases.